Vibrational near-field mapping of planar and buried three-dimensional plasmonic nanostructures - Drégely, Daniel; Neubrech, Frank; Duan, Huigao; Vogelgesang, Ralf; Giessen, Harald (Nature Communications, 2013)
Nanoantennas confine electromagnetic fields at visible and infrared wavelengths to volumes of only a few cubic nanometres. Assessing their near-field distribution offers fundamental insight into light-matter coupling and is of special interest for applications such as radiation engineering, attomolar sensing and nonlinear optics. Most experimental approaches to measure near-fields employ either diffraction-limited far-field methods or intricate near-field scanning techniques. Here, using diffraction-unlimited far-field spectroscopy in the infrared, we directly map the intensity of the electric field close to plasmonic nanoantennas. We place a patch of probe molecules with 10 nm accuracy at different locations in the near-field of a resonant antenna and extract the molecular vibrational excitation. We map the field intensity along a dipole antenna and gap-type antennas. Moreover, this method is able to assess the near-field intensity of complex buried plasmonic structures. We demonstrate this by measuring for the first time the near-field intensity of a three-dimensional plasmonic electromagnetically induced transparency structure.